IMPROVING SPEAKING SKILL THROUGH INSIDE-OUTSIDE CIRCLE TECHNIQUE OF THE TENTH GRADE STUDENTS OF SMA N 8 DENPASAR - Madra, I Nyoman (Yavana Bhasha : Journal of English Language Education, 2018)
The objective of the present study is to find out whether or not speaking skill of thetenth-gradestudents of SMA N 8 Denpasar can be improved through Inside-Outside Circle.This also helps the students to think critically about a topic. A scientific research should havean objective of study because it can make the research being useful and directed. Theobjective of the present study is to find out whether or not speaking skill of the tenth-gradestudents of SMA N 8 Denpasar can be improved through Inside-outside circle. The presentstudy was a classroom action research (CAR) as a research design which concerns withteaching speaking through Inside-outside Circle. In the present study, the teaching andlearning process was a cyclical process and divided into some cycles where each cycleconsisted of some interrelated activities such as planning, action, observation, and reflection.The research instruments which were used in this study were a test (pre-test and post-test),and questionnaire. Based on the findings, the pre-existing data showed that the subjects stillhad low skill in English especially in speaking. The result of the pre-test showed that only 9subjects can pass the minimum passing grade. In line with the post-test of the cycle I, thedata showed that 22 subjects could pass the minimum passing grade. Finally, the post-testof cycle II showed that there were 32 subjects who passed the minimum passing grade. Theincreasing mean score showed that the subjects? speaking skill could be improved byimplementing Inside-outside Circle.